+0

# INTIGRATION

0
153
1

(cotx/sinx-tan^2x- tanx/cos+2x/cos^2x)dx

Guest Aug 29, 2017

#1
+91435
+3

(cotx/sinx-tan^2x- tanx/cos+2x/cos^2x)dx

NOTE I have added an x after cos as I think that you forgot it.  :)

$$\int (\frac{cotx}{sinx}-tan^2x-\frac{ tanx}{cosx}+\frac{2x}{cos^2x})dx\\ =\int \frac{cotx}{sinx}dx-\int tan^2x dx-\int\frac{ tanx}{cosx} dx+\int\frac{2x}{cos^2x}dx\\ =\int \frac{cotx}{sinx}dx-\int tan^2x dx-\int\frac{ tanx}{cosx} dx+\int\frac{2x}{cos^2x}dx\\~\\ -----\\ \int \frac{cotx}{sinx}dx=\int \frac{cosx}{sin^2x}dx=\int cosx(sinx)^{-2}dx=-(sinx)^{-1}+c_1=-cosecx+c_1\\ \int tan^2x dx=\int \frac{sin^2x}{cos^2x} dx=\int\;(sec^2x-1)dx=tanx-x+c_2\\ \int\frac{ tanx}{cosx} dx=\int\frac{ sinx}{cos^2x} dx=(cosx)^{-1}+c_3=secx+c_3\\~\\ \text{So far I have }\\ =\:-cosecx-(tanx-x)-(secx)+\int\frac{2x}{cos^2x}dx\\ =\:-cosecx-tanx+x-secx+\int\frac{2x}{cos^2x}dx$$

$$=\:-cosecx-tanx+x-secx+\int\frac{2x}{cos^2x}dx\\ consider\;\;\;\int\frac{2x}{cos^2x}dx\\ =\int(2x(sec^2x)dx\\ \text{Solve using integration by parts}\\ u=2x \qquad v'=sec^2x\\ u'=2 \qquad v=tanx\\ \int\;uv'dx=uv-\int(vu')dx\\ =2xtanx-\int(2tanx)dx\\ =2xtanx-2\int(\frac{sinx}{cosx})dx\\ =2xtanx+2ln(cosx))+c_4\\~\\ \text{So my final answer is}\\ =\:-cosecx-tanx+x-secx+2xtanx+2ln(cosx)+c\\$$

Melody  Aug 29, 2017
Sort:

#1
+91435
+3

(cotx/sinx-tan^2x- tanx/cos+2x/cos^2x)dx

NOTE I have added an x after cos as I think that you forgot it.  :)

$$\int (\frac{cotx}{sinx}-tan^2x-\frac{ tanx}{cosx}+\frac{2x}{cos^2x})dx\\ =\int \frac{cotx}{sinx}dx-\int tan^2x dx-\int\frac{ tanx}{cosx} dx+\int\frac{2x}{cos^2x}dx\\ =\int \frac{cotx}{sinx}dx-\int tan^2x dx-\int\frac{ tanx}{cosx} dx+\int\frac{2x}{cos^2x}dx\\~\\ -----\\ \int \frac{cotx}{sinx}dx=\int \frac{cosx}{sin^2x}dx=\int cosx(sinx)^{-2}dx=-(sinx)^{-1}+c_1=-cosecx+c_1\\ \int tan^2x dx=\int \frac{sin^2x}{cos^2x} dx=\int\;(sec^2x-1)dx=tanx-x+c_2\\ \int\frac{ tanx}{cosx} dx=\int\frac{ sinx}{cos^2x} dx=(cosx)^{-1}+c_3=secx+c_3\\~\\ \text{So far I have }\\ =\:-cosecx-(tanx-x)-(secx)+\int\frac{2x}{cos^2x}dx\\ =\:-cosecx-tanx+x-secx+\int\frac{2x}{cos^2x}dx$$

$$=\:-cosecx-tanx+x-secx+\int\frac{2x}{cos^2x}dx\\ consider\;\;\;\int\frac{2x}{cos^2x}dx\\ =\int(2x(sec^2x)dx\\ \text{Solve using integration by parts}\\ u=2x \qquad v'=sec^2x\\ u'=2 \qquad v=tanx\\ \int\;uv'dx=uv-\int(vu')dx\\ =2xtanx-\int(2tanx)dx\\ =2xtanx-2\int(\frac{sinx}{cosx})dx\\ =2xtanx+2ln(cosx))+c_4\\~\\ \text{So my final answer is}\\ =\:-cosecx-tanx+x-secx+2xtanx+2ln(cosx)+c\\$$

Melody  Aug 29, 2017

### 21 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details